Translational research in breast cancer : biomarker diagnosis, targeted therapies and approaches to precision medicine - Song, Erwei; Hu, Hai (Springer, 2017)
"This book offers a comprehensive introduction to translational efforts in breast cancer, addressing the latest approaches to precision medicine based on the current state of understanding of breast cancer. With the latest developments in breast cancer research, our understanding of the genomic changes and the oncogenic signaling cascade of breast cancer has made considerable strides. Further, the immuno-environment has been demonstrated as the barrier to clinical cancer. As a result of these two trends, a clearer picture of the molecular landscape of breast cancers has facilitated the development of diagnostic, prognostic and predictive biomarkers for clinical oncology. All these aspects are addressed in this volume, which offers a comprehensive resource for researchers, graduate students and oncologists in cancer research"--Publisher's description.
Keywords: Breast -- Cancer.; Breast -- Cancer -- Diagnosis.; Breast -- Cancer -- Treatment.; Biochemical markers.; elektronické knihy; electronic books